Runoff and channel way water balance of small rivers in Аlmaty within unban areas (Journal of Geography and Environmental Management, 2016)
There were given the results of studies of the annual water runoff characteristics of small rivers in Almaty for a longterm period using available data of inventory submissions of “Kazhydromet” for the entire observation period including 2011 and taking into account the impact of agricultural economy activity. As well there were analyzed the results of studies of the channel water balance of small city rivers within its borders that were conducted in 2006, 2007 and 2013 in order to identify areas of abstraction losses in the streamflow, and areas of groundwater seepage into the rivers channel ways.